An anti-takeover strategy by limitation of voting rights: A model and a numerical approach - Moschetto, Bruno-Laurent; Teulon, Frédéric (Management international / International Management / Gestiòn Internacional, 2015)
This study develops a new trade-off view of corporate governance from an examination of rules that limit voting rights as a defensive measure against a hostile takeover attempt. The theoretical framework concerns a listed company, the capital of which is mainly detained by atomistic shareholders and the power of which is in the hands of a minority shareholders, the hard core. The latter wants to block any hostile takeover and constructs a device based on two parameters allowing it to act on the limitation of the voting rights: a threshold and a scale-down coefficient.